Management of Pre-existing Macular Edema With Intravitreal Dexamethasone Implant in Eyes Undergoing Cataract Surgery. (July 2019) - Smith, Bradley T.; Banda, Himanshu K.
Purpose: The purpose of this study was to assess the efficacy and safety of intraocular dexamethasone implant (IDI) for pre-existing macular edema due to retinal vein occlusion (RVO), diabetes, and uveitis in eyes undergoing cataract surgery. Methods: A retrospective, noncomparative study was conducted. The medical record database was searched for patients meeting criteria of macular edema treated with IDI prior to cataract surgery. Results: Twenty-two patients had macular edema due to RVO (14 or 63.6%), diabetes (5 or 22.7%), or uveitis (3 or 13.6%). None had complications during cataract surgery. Thirteen (60%) were female with a mean age of 64 years (range, 25-82 years). The mean interval of dexamethasone implantation to cataract extraction was 49 days. The mean interval to follow-up optical coherence tomography was 65 days. Mean logarithm of the minimum angle of resolution (logMAR) visual acuity (VA) improved from .94 (20/150–) to .56 (20/70+) ( P = .004), with an average gain in VA measuring +0.37 logMAR (3 line gain). Mean central retinal thickness decreased from 474 to 378 μm ( P = .006) with an average reduction of 96 μm ( P = .006). Mean macular volume decreased from 10.29 mm 3 to 9.78 mm 3 ( P = .0002) with an average reduction of 0.51 mm 3 . Two patients developed postoperative ocular hypertension requiring treatment with topical antihypertensive agents. One had a combined glaucoma filtering procedure at the time of cataract surgery because of a history of ocular hypertension. Conclusions: The majority of this cohort had improved macular edema due to RVO, diabetes, and noninfectious uveitis while undergoing cataract surgery. IDI is an effective and safe treatment in these at-risk eyes.